2005
DOI: 10.1021/cg0497344
|View full text |Cite
|
Sign up to set email alerts
|

SAXS Study of the Nucleation of Glycine Crystals from a Supersaturated Solution

Abstract: Nucleation of crystalline solids, the first stage of crystallization from solution, is not yet fully understood. This is true for both small molecules of low molecular weight and more complicated large molecules. To obtain direct structural information about the process of nucleation and crystallization of small molecules, smallangle X-ray scattering (SAXS) has been used to study the crystallization of the amino acid glycine from its supersaturated aqueous solution. The scattering data was analyzed using the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
148
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(158 citation statements)
references
References 34 publications
8
148
1
1
Order By: Relevance
“…The first example came from experimental studies of lysozyme crystals, which were found to crystallize more easily just outside the metastable gas-liquid phase separation transition [96,97]. Similar processes have been found in both small molecules, like glycine [98] and calcium carbonate [91], and colloidal systems [88]. Two-step crystallization in absence of a metastable liquid phase was also confirmed theoretically in spin models [99] and density functional theory [93].…”
Section: Two-step Nucleation: Coupling Between Density Fluctuatiomentioning
confidence: 67%
“…The first example came from experimental studies of lysozyme crystals, which were found to crystallize more easily just outside the metastable gas-liquid phase separation transition [96,97]. Similar processes have been found in both small molecules, like glycine [98] and calcium carbonate [91], and colloidal systems [88]. Two-step crystallization in absence of a metastable liquid phase was also confirmed theoretically in spin models [99] and density functional theory [93].…”
Section: Two-step Nucleation: Coupling Between Density Fluctuatiomentioning
confidence: 67%
“…The number and variety of solutions that have been found to crystallize from dense liquid precursors lead to the idea that two-step crystallization pathways are quite universal crystallization processes. For example, two-step crystallization processes have been suggested for systems outside the region of stability of the dense fluid phase [38,41,[45][46][47][48].…”
Section: Two-step Nucleation and Precursorsmentioning
confidence: 99%
“…A magnetic stirrer bar was added to each test tube, which was then promptly sealed to prevent solvent evaporation and contamination. The test tubes were then moved directly to a second thermostatic bath at a temperature corresponding to a slight undersaturation with respect to form I (52, 55 or 60 °C) for a controlled period of time (8,30 or >360 min). The temperature levels and time limits are marked with horizontal and vertical lines, respectively, in Figure 3.…”
Section: Cooling Crystallizationsmentioning
confidence: 99%